Experimental investigation on dynamic failure of carbon/epoxy laminates under underwater impulsive loading. (May 2018) - Ren, Peng; Zhou, Jiaqi; Tian, Ali; Ye, Renchuan; Shi, Lu; Zhang, Wei; Huang, Wei
Abstract: The dynamic response and failure modes of carbon/epoxy laminates subjected to underwater impulsive loading are experimentally investigated in this work. The effects of impulse intensity and fluid-structure interaction (FSI) on the failure modes of the clamped laminates were also assessed. A lab-scale underwater explosive simulator was utilized to impart the controlled impulsive loading with three different decay times on the laminates. The 3D Digital Image Correlation method with high speed photography was used to capture the dynamic response of the laminates. A series of microscopic examinations was conducted to analyze the failure mechanism of the laminates. The results show that the composite laminates provided higher blast resistance than aluminum plates in the same thickness. The fiber breakage, delamination and matrix crack were the main failure modes of the laminates subjected to underwater impulsive loading. The fiber breakage occurring at the center and the boundary of the plate was mainly caused by the stretching and shear-off, respectively. The damage extent of the laminates was increased with the impulsive loading increasing or FSI parameter decreasing. The results obtained in this study provide a potential application guidance for laminates in marine structure lightweight design. Highlights: The dynamic failure of carbon/epoxy laminates under underwater impulsive loading was investigated by using the FSI experiments. DIC was used to capture the dynamic response of composite laminates. Effects of impulse of underwater shock loading and fluid-structure interaction on the failure modes were investigated. Multi-scale failure mechanism was examined.